Morphology of leaves and content of secondary metabolites asiaticoside in some accession of pegagan (Centella asiatica l. Urban) in North Sumatera - Noverita Sprinse Vinolina; Luthfi A. M. Siregar (Syiah Kuala University, 2012)
The objectives of this experiment was to observe morphology of leaves and content of asiaticoside in some accessions of Centella asiatica of lowland Sumatera Utara, Medan and Pantai Labu Deli Serdang and the highlands of Sumatera Utara, Berastagi, Kabanjahe and Samosir. The study also examines the link between altitude grow with the content of asiaticoside of Centella asiatica. Domestication research include: exploration and collection. This activity is carried out to collect Centella asiatica from different geographic locations with different altitudes. Later examination asiaticoside levels in the leaves of Centella asiatica by HPLC method and phytochemical test. Analysis of soil at all growing places were also conducted. The highest content of asiaticoside in accessions of Centella asiatica tested is as follows accession Deli Serdang (2.38%), Kabanjahe (1.43%), Medan (1.38%), Berastagi (1.38%), Samosir with shade (0.28%) and accession Samosir (0.24%). Altitude does not affect the content of asiaticoside Centella asiatica because in this study obtained the highest asiaticoside content found on lowland accessions namely (± 4 m asl), namely accession Pantai Labu Deli Serdang (2.38%).